Evaluation of the fractures of asphalt concrete added with rubber particles based on the fine aggregate mixtures. (16th May 2022) - Zu-yuan, Li; Hou-zhi, Wang; Chen-guang, Shi; Xing, Cai; Jun, Yang; Yun-hong, Yu
Highlights: Research on crack resistance of fine aggregate mixture (FAM) added with rubber particles. The analysis of the crack resistance of FAMs based on the Semicircle bending test and AE technology. The use of AE signals to evaluate the cracking process of FAM mixed with rubber particles. Abstract: In railway construction, the solidified track bed has gained significant attention from researchers in recent years. Asphalt concrete added with rubber particles is a substitute for the polyurethane cured track bed. In this study, two fine aggregate mixtures (FAM) for different asphalt concrete mixed with rubber particles as the material for the solidified trackbed have been evaluated. Semicircle bending (SCB) test and CT scanning were used to evaluate the mechanical properties of four FAM. Acoustic emission (AE) was used to collect the AE signals during the SCB test. The energy analysis results of AE reveal that the temperature sensitivity of epoxy-FAM is better than that of rubber-FAM. Further, the AE signals can be classified according to the cracking type by clustering analysis. The results demonstrate that the epoxy-FAM with 11% rubber content has the best fracture resistance. AE technology provides an effective evaluation of the microscopic cracking process of FAM.